Tanghod a transient modular field research facility for biodiversity - Yadao, Kim Hazel B.; Chua, Johannes Vincent (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
Philippines, although a developing country, is rich in people, culture and natural resources. It is faced with many issues and problems such as substandard developments, unmaximized land uses and unoriginal economic strategies. Yet the very dtrenth in which the country can anchor for progress is in its geographic nature: Archipelagic, Tropical Climate, Rain and Wetlands, and Wild Forests -- all of which account for the Philippines being rich in Biodiversity. But then, despite having this richness, we are the hottest of hotspots. We ranked first in the list of countries with deteriorating biodiversity. And so, this research project was undertaken to make the conservation of our Biodiversity known to many, and help strengthen field research initiatives and general public engagement. Tanghod is an architectural design for a transient biodiversity research and engagement hub, a localized transportable research and awareness facility to advance, spread and strengthen knowledge, skills, interest and initiatives for biodiversity in a community level. Using the concepts of transiency, modularity and creating a collaborative environment, Tanghod will be made of laboratory modules that may be transported and located to different remote sites with high concentration of biodiversity. Particularly, a hypothetical site was chosen as a model site: San Andres, Verde Island, Batangas -- an island close to Verde Island Passage, the Center of Center of Marine Biodiversity in the world. Tanghod showcases a flexible architectural solution and contribution to protecting and exploring the country's vast biodiversity.
include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Biodiversity research center; Biodiversity facility -- Architectural design